2007
DOI: 10.1109/tcapt.2007.898376
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Performance of Thermoelectric Coolers Through the Application of Distributed Control

Abstract: Abstract-The primary drawback of thermoelectric coolers (TECs) for electronics cooling applications is their thermodynamic inefficiency due to material limitations. The present work considers a control strategy to improve the overall coefficient of performance in an engineering system instead of addressing material shortcomings. Typical TECs are composed of several individual thermocouples that are powered in series and remove heat in parallel. If one of the numerous thermocouples is powered, all the thermocou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…Thermoelectric cooler(or TEC in abbreviation) can realize refrigeration or heating by changing the direction of current, and has the advantages of small volume, no need of refrigerant and moving parts, which is very convenient for the multi-parameter combined environmental test. The refrigeration coefficient of TEC is smaller than that of refrigeration compressor [6,7], but it has a heating coefficient larger than 1.0, which is very fit for heating.…”
Section: Structure Of Temperature Testing Systemmentioning
confidence: 94%
“…Thermoelectric cooler(or TEC in abbreviation) can realize refrigeration or heating by changing the direction of current, and has the advantages of small volume, no need of refrigerant and moving parts, which is very convenient for the multi-parameter combined environmental test. The refrigeration coefficient of TEC is smaller than that of refrigeration compressor [6,7], but it has a heating coefficient larger than 1.0, which is very fit for heating.…”
Section: Structure Of Temperature Testing Systemmentioning
confidence: 94%
“…The idea can be developed backward and consider whether it would be reasonable to use distributed control for the separated elements of TEC. This scheme would lead to the more efficient use of TEC and higher value for COP [16].…”
Section: A Steady-state Condition Simulationmentioning
confidence: 99%
“…Bell [14] has shown that individually controlling the current to the thermocouples in a TEM or individual TEMs in an array of them may increase efficiency when TEMs are used to transfer heat between two fluid streams. Moreover, Harvey et al [15] have shown that efficiency may be increased substantially by supplying the optimal current to each thermocouple in a TEM subjected to a non-uniform heat load with a specified maximum temperature. Additionally, Hodes [16] showed that for precision temperature control applications that, depending on operating conditions, require either Peltier cooling at the csi (where an efficient heat sink is of benefit) or Peltier heating at the csi (where a less efficient heat sink is optimal), judicious selection of heat sink thermal resistance can significantly reduce the maximum power consumption of a TEM.…”
Section: Enhancement Of Thermoelectric Refrigerationmentioning
confidence: 99%